Prevalence of Premature Ejaculation among Patients with Type 2 Diabetes in Abha City, Saudi Arabia - Al Ghanem, Turki Abdullah; Alqahtani, Mohammed Mushabab; Alqahtani, Abdullatif Saeed; Aldosari, Rajis Nasser; Al Ahmree, Abdullah Oudah; Al-kzman, Ali Ayed Falah; Al Saleh, Majed; Al-Asmari, Bandar; Alshaikh, Ayoub (Journal of Neonatal Surgery, 2025)
Background/Objectives: Premature ejaculation (PE) is a common sexual disorder, particularly among patients with type 2 diabetes mellitus (T2DM). The objective of this study was to assess the prevalence and severity of PE among married men with T2DM in Abha City, Saudi Arabia, and determine the sociodemographic and personal factors for PE. Methods: A cross-sectional study using a self-completion questionnaire was carried out between January 2024 and July 2024 among married men aged 18 years and older with established T2DM who live in Abha City, Saudi Arabia. PE was assessed by the valid and reliable Arabic Index of the Premature Ejaculation Scale (AIPE). The values of Intravaginal Ejaculation Latency Time (IELT) were used in assessing the level of severity among the participants. Results: There were 344 patients in the study. PE was highly prevalent in the study, and 33.4% of them had moderate PE, while 63.4% had mild-to-moderate PE. Severe PE was found in 2% of the participants. AIPE and IELT scores indicated the extent of distress caused by PE, especially from the age group 31-40 years and in participants who were in the age group 25-30 years. Sociodemographic variables such as age, education, occupation, and income were independently associated with PE severity. Conclusion: High prevalence of probable PE was found among Saudi diabetic patients in this study. Increased awareness and targeted interventions are needed to enable management of PE among T2DM patients.